Perspective of Development Law on the Impact of Investment in the Mandalika Circuit Project in Indonesia - Almira Balqis (Universitas Muhammadiyah Surakarta, 2023)
The Mandalika circuit project is a development project for international standard sports facilities and of course is also supported by the various advantages that Lombok, West Nusa Tenggara has. In fact, for the first time after the Mandalika project was built, it will be used in world level competitions, namely Superbike (WSBK), Grand Prix (MotoGP). The development of the project has of course attracted attention both nationally and internationally, so it is not surprising that it will attract investors to invest their capital in Indonesia, especially for the Mandalika Circuit Development Project, Lombok. So that these investment activities will have impacts for and on Indonesia and the surrounding population. So, through this article, the author seeks to find out what impacts are caused and then elaborates on the views of Prof. Dr. Mochtar Kusumaatmadja's concept of development law. This writing uses a normative juridical approach which refers to statutory regulations, legal norms, and literature study. The concept of development law advocated by Prof. Mochtar is to make law (various investment regulations in the Mandalika project) a means/tool for societal renewal (change). Through the application of rules or regulations (law as a tool of social engineering) for continuity of activity direction the desired community in development. The role of law in the development of the Mandalika project is expected to ensure that these changes take place in an orderly manner with the aim of achieving order which is one of the classic functions of law.